استخدام الوسائل السمعية والبصرية في اللغة العربية التعلم على محارة قراءة - Sofiyah, Siti Sofi (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2022)
With the development of an increasingly modern era, Arabic is now able to adapt. In learning Arabic using conventional methods that are boring for students are still applied in schools. With the development of the times, it is hoped that teachers will be able to create a pleasant learning atmosphere and be able to make the best use of learning media. One way that is used in utilizing Arabic learning is easily called audio-visual media. From teacher directions to students to visit websites on the internet with ease and fun supported by technological developments. In this study, the researcher used qualitative research, however, quantitative methods were used to calculate the questionnaire data, which were then processed into qualitative ones to describe the data. Likewise, the data collection techniques used in this study were observation, questionnaires, and documentation. Keywords: Learning Media, Arabic, Audio Visual